Game-Theoretic Strategy Design of Multistatic MIMO Radar Network and Jammer - Zhang, Gangsheng; Xie, Junwei; Zhang, Haowei (IEEE transactions on aerospace and electronic systems, 2024)
This article investigates the game-theoretic strategy design problem between multistatic multiple-input-multiple-output (MIMO) radar network and jammer. We consider a radar network organized into multiple statistical MIMO radars. The conflict between the jammer and the radar network is described as a two-player zero-sum game because of their adversarial nature. Mutual information (MI) is used as the utility function where the radar network and the jammer can change their power allocation strategy so that the MI is optimized for the two players prospectively. The unilateral, hierarchical, and symmetric games are studied from the perspective of the Game theory, and the equilibria solutions are derived, respectively. Finally, we present simulation results and compare the performances with other strategies.